Lexical Cohesion and Corpus Construction in Primary and Secondary School English Teaching - Zhou, Haiming; Liu, Qin (International Research in Education, 2022)
English learning in primary and secondary schools is the critical period of language acquisition, which is very important for developing students’ language ability. Among them, vocabulary teaching cohesion is the basis of English learning, which affects students’ learning at different stages to a great extent. In the process of English learning, if the teaching vocabulary cohesion is not reasonable, it will not only reduce students’ learning efficiency, but also affect students’ ability training in listening, speaking, reading and writing skills. This paper studies the lexical cohesion in primary and secondary school English teaching and constructs the corresponding lexical corpus.